Identifikasi Faktor Pendukung Kesiapan Karir Siswa SMKN 4 Kota Jambi - Nisak Khori Aprilyani; Rasimin Rasimin; Siti Amanah (Journal on Education, 2023)
One of the most important things to do in adolescence is to prepare for a future career. The fact on the ground indicates that the lack of support in career preparedness and still lack the courage to develop in that career preparedness matches our potential and abilities. The study aims to find out how the students' career preparedness factor is in the 4 cities of jambi. The method used is a quantitative method using a descriptive approach. The study is done to represent the square in its own right. The number of samples in this study is 68 student responders taken through random sampling techniques. The data-collection technique USES an angket with a cloned model with a two-pronged answer.